대기압 유전체배리어방전으로 합성 및 산화 처리된 SiOxCy(-H) 박막의 부식방지 특성 - 김기택(Gi-Taek Kim); 김윤기(Yoon Kee Kim) (Biuletyn Uniejowski, 2020)
A SiOxCy(-H) thin film was synthesized by atmospheric pressure dielectric barrier discharge(APDBD), and a SiO2-like layer was formed on the surface of the film by oxidation treatment using oxygen plasma. Hexamethylcyclotrisiloxane was used as a precursor for the SiOxCy(-H) synthesis, and He gas was used for stabilizing APDBD. Oxygen permeability was evaluated by forming an oxidized SiOxCy(-H) thin film on a PET film. When the single-layer oxidized SiOxCy(-H) film was coated on the PET, the oxygen gas permeability decreased by 46% compared with bare PET. In case of three-layer oxidized SiOxCy(-H) film, the oxygen gas permeability decreased by 73%. The oxygen permeability was affected by the thickness of the SiO2-like layer formed by oxidation treatment rather than the thickness of the SiOxCy(-H) film. The excellent corrosion resistance was demonstrated by coating an oxidized SiOxCy(-H) thin film on the silver-coated aluminum PCB for light emitting diode (LED).